THE INDEX EVALUATION OF PHYSICAL DEVELOPMENT BY RURAL STUDENTS - Валентина Сергеевна Гладкая; Вера Людвиговна Грицинская (Мать и дитя в Кузбассе, 2017)
The aim of the exploration was to reveal the peculiarities of physical development of rural students living in the southern districts of the Krasnoyarsk territory.